Quantum tomography of electrical currents - R. Bisognin (Nature Portfolio, 2019)
Elementary excitations of electronic devices have potential use in quantum information but control and readout capabilities are not as developed as they are for more mature systems such as photonic qubits. Here the authors develop and demonstrate a tomographic protocol for electron and hole wavefunctions.